The role of knowledge-sharing behaviour in the relationship between the knowledge creation process and employee goal orientation - Kattareeya Prompreing; Clark Hu (International Journal of Business Science & Applied Management (IJBSAM), 2021)
This study examines the structural relationship among four distinctive forms of the knowledge creation process, namely socialization, externalization, combination, and internalization; two distinctive types of knowledge-sharing behaviours, namely collecting and donating; and employee goal orientation. Data were collected through a survey from 390 employees in the hospitality business, and the Structural Equation Modelling (SEM) technique was adopted to test the proposed hypotheses. The findings suggest that (1) socialization and combination have a positive relationship with knowledge collecting and knowledge donating; (2) externalization does not support knowledge collecting but has a positive relationship with knowledge donating; (3) internalization supports neither knowledge collecting nor knowledge donating; (4) knowledge collecting has a negative relationship with learning orientation but has a positive relationship with performance orientation; (5) knowledge donating has a positive relationship with both learning and performance orientation. Thus, knowledge-sharing behaviour was found to have an impact on employees' goal orientation. The study concludes with discussions of the research findings, managerial implications, and limitations. We also suggest expanding research on this topic.
Keywords: 650; employee goal orientation; hospitality businesses; knowledge management; knowledge creation process; knowledge-sharing behaviour